Ilustrasi Surah Al-Waqi’ah sebagai Media Pengenalan Al-Qur’an bagi Anak di Tingkat Sekolah Dasar - Hanani Hanani; Ariusmedi Ariusmedi (Lembaga Pengembangan Kinerja Dosen, 2024)
Surah Al-Waqi’ah is one of the surahs in the Koran. This surah is in the 27th Juz. And is the 56th surah in the Al-Quran. Surah Al-Waqi’ah consists of 96 verses. Surah Al-Waqi’ah has still not been detected being introduced to children. In fact, studying surah Al-Waqi’ah has many functions. One of them is started in the hadith of Al-Baihaqi. This surah contains many lessons and wisdom that readers can take. Therefore, surah Al-Waqi’ah is deemed suitable to be introduced to children with an illustrated book. With the help of illustrations, children can better understand the contents of the reading in surah Al-Waqi’ah. This design uses the Glass Box method with several stages, like stage of preparation, incubation, illumination and verification.